THE EFFECT OF IDEALISM, LOVE OF MONEY, AND AGE OF ACCOUNTING STUDENTS ON THE ETHICAL PERCEPTION OF ACCOUNTING STUDENTS - Muhammad Daffa Rasyadan; Endah Susilowati (International Journal of Economy, Education and Entrepreneurship, 2023)
This study aims to examine and prove the influence of idealism, love of money, and age of accounting students on accounting students' ethical perceptions. In this study, the method used is a quantitative approach with the approach used in this study using aspects of processing through statistical methods with numerical data base. The population as well as the sample used in this study were all accounting students at UPN Veterans East Java. The type of data used in this study used primary data obtained directly from 93 respondents of UPN Veteran East Java accounting students. The research data source came from collecting questionnaires which were distributed via the Google Form platform and distributed via the WhatsApp Group of UPN Veteran East Java accounting students. The data analysis technique used in this study is Partial Least Squares (PLS) with the help of SmartPLS software. The results of the study show that idealism and age influence the ethical perceptions of accounting students. Meanwhile, the Love of Money has no effect on the Ethical Perceptions of Accounting Students